IMPLEMENTASI DAN AKTUALISASI PENDIDIKAN HUMANIS RELIGIUS DI SEKOLAH - Sri Haryanto; Achmad Zainuri Rosid (Jurnal Cakrawala Ilmiah, 2023)
The research method used by the researcher in this research is a qualitative approach with a descriptive method. This type of research uses a literature study. Education in Indonesia is still experiencing a character crisis, many violations of norms, juvenile delinquency and far from religious values. Conceptualization of the image of a religious humanist school, namely a school that develops basic humanist values ​​(freedom, creativity, cooperation, honesty, self-actualization) while remaining within a religious framework. Not secular humanism, but humanism by religious values ​​(science, aqidah, worship, morality, ma'rifah). Factors that describe a religiously humanist school include the principal as a motivator, teachers as a motivator, a variety of activity programs, adequate learning facilities, a conducive school culture, a supportive social environment, and responsive parents.